All-solid secondary battery
The introduction of a buffer layer between battery units in all-solid-state secondary batteries addresses uneven pressure issues, enhancing battery durability by reducing cracks and improving cycle characteristics.
Patent Information
- Application Number
- JP2020081818
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-05-07
AI Technical Summary
In stacked all-solid-state secondary batteries, uneven pressure application during charging and discharging leads to cracks and deformation in the electrolyte layer, deteriorating battery characteristics.
A buffer layer is provided between adjacent battery units to disperse pressure and absorb volume changes, ensuring the total thickness of the buffer layer exceeds the thickness change of the battery units due to charging and discharging.
Reduces uneven pressure on battery units, preventing cracking and deformation of the electrolyte layer, thereby improving battery characteristics such as cycle performance.
Smart Images

Figure 0007609569000001 
Figure 0007609569000002 
Figure 0007609569000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state secondary battery. [Background technology]
[0002] In recent years, all-solid-state secondary batteries using a solid electrolyte as the electrolyte have been attracting attention (for example, Patent Document 1). In all-solid-state secondary batteries, the electrolyte layer is formed by compressing solid electrolyte powder during production.
[0003] Incidentally, as such an all-solid-state secondary battery, a stacked type battery is known that is constructed by stacking a plurality of battery units (also called single cells) each having a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in this order. In this stacked type all-solid-state secondary battery, when charging and discharging are repeated, each battery unit expands and contracts repeatedly, and adjacent battery units exert pressure on each other. Here, the amount of expansion and contraction of each battery unit is not uniform in the in-plane direction of the stacking (direction perpendicular to the stacking direction) but is biased, so that each battery unit is subjected to uneven pressure in the in-plane direction of the stacking. As a result, when charging and discharging are repeated, cracks and deformations gradually occur in the electrolyte layer of each battery unit, resulting in a problem that battery characteristics such as cycle characteristics are deteriorated. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-086554 A Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, an object of the present invention is to reduce the bias in pressure applied to each battery unit during charging and discharging in a stacked-type all-solid-state secondary battery. [Means for solving the problem]
[0006] That is, the all-solid-state secondary battery of the present invention is a stacked-type all-solid-state secondary battery in which a plurality of battery units, each of which is constituted by stacking a positive electrode layer, a solid electrolyte layer, and a negative electrode layer in this order, are stacked along the stacking direction, and a buffer layer is provided between adjacent battery units.
[0007] In this configuration, since a buffer layer is provided between adjacent battery units, when the battery units expand due to charging of the all-solid-state secondary battery, the pressure can be dispersed, and the bias of the pressure applied to each battery unit due to charging and discharging can be reduced. This makes it possible to suppress cracks and deformations in the electrolyte layer caused by repeated charging and discharging, and to suppress deterioration of battery characteristics such as cycle characteristics.
[0008] In the all-solid-state secondary battery, it is preferable that a total thickness of the buffer layers along the stacking direction is greater than a total amount of change in thickness of the battery units along the stacking direction due to charging and discharging. In this way, the change in thickness of the battery unit due to charging and discharging can be reliably absorbed by the buffer layer, and the unevenness of the pressure applied to each battery unit due to charging and discharging can be further reduced.
[0009] The "amount of change associated with charging and discharging" here means the amount of change when the all-solid-state battery is changed from a fully charged state to a discharged state. In the present invention, the "fully charged state" means a state in which the SOC (State Of Charge) of the all-solid-state battery is 90% or more, and the "discharged state" means a state in which the SOC of the all-solid-state battery is 10% or less. The "SOC of the all-solid-state battery" means the ratio of the "total value of the remaining capacity of each battery unit" to the "total value of the rated capacity of each battery unit." In addition, the "total thickness of the buffer layers" means the total thickness of the buffer layers when the all-solid-state secondary battery has multiple buffer layers, and means the thickness of the single buffer layer when the all-solid-state secondary battery has only one buffer layer. Moreover, the "total amount of change in thickness of the battery units" means the total amount of change in thickness of all the battery units included in the all-solid-state secondary battery.
[0010] A specific embodiment of the all-solid-state secondary battery is one in which the battery unit performs charging and discharging by transferring lithium ions between the positive electrode layer and the negative electrode layer.
[0011] The buffer layer preferably has a smaller elastic modulus than the positive electrode layer and the negative electrode layer. In this way, when the battery unit expands due to charging and discharging, the buffer layer can elastically deform and more reliably absorb the volume change of the battery unit, thereby further reducing the unevenness of the pressure applied to each battery unit.
[0012] As an aspect in which the effects of the present invention are prominently exhibited, it is preferable that the total value of thicknesses of the positive electrode layer, the solid electrolyte layer, and the negative electrode layer along the stacking direction of the all-solid-state secondary battery is larger in a fully charged state than in a discharged state.
[0013] As an aspect in which the effects of the present invention are prominently exhibited, it is desirable that the all-solid-state secondary battery is in a state in which a metallic lithium layer is precipitated between the negative electrode current collector and the negative electrode active material layer included in the negative electrode layer in a fully charged state. In addition, in the all-solid-state secondary battery, in a fully charged state, it is preferable that a total value of thicknesses, along the stacking direction, of the negative electrode current collector and the negative electrode active material layer included in the negative electrode layer is smaller than a thickness, along the stacking direction, of a metallic lithium layer precipitated between the negative electrode current collector and the negative electrode active material layer. This is preferable because the volumetric energy density at full charge is high and dissolution and deposition of lithium can be repeated stably.
[0014] In an embodiment in which the effects of the present invention are particularly remarkable, the all-solid-state secondary battery has a specific capacity per unit area of the positive electrode layer of X [mAh / cm 2], the thickness of the metallic lithium layer in the stacking direction in a fully charged state can be 4.85×X [μm] or more.
[0015] It is preferable that the all-solid-state secondary battery further includes a rectangular parallelepiped case that houses the plurality of battery units and the buffer layer, and that the plurality of battery units and the buffer layer are housed in the case so as to be stacked along a height direction, with a bottom surface being an opposing surface having the smallest area among three sets of opposing surfaces of the case. In this way, it is possible to further reduce the unevenness of the pressure applied to each battery unit when the battery unit expands due to charging and discharging.
[0016] In one embodiment of the all-solid-state secondary battery, the area of the buffer layer is larger than the area of the battery unit when viewed from the stacking direction.
[0017] In one embodiment of the all-solid-state secondary battery, the battery units are connected in parallel with each other, and the buffer layer provided between the battery units is made of an insulating material. In this case, it is preferable that an insulating film having a thickness smaller than that of the buffer layer is provided between the adjacent battery units and the buffer layer.
[0018] In another embodiment of the all-solid-state secondary battery, the battery units are connected in series to each other, and the buffer layer provided between the battery units is made of a conductive material. Effect of the Invention
[0019] According to the present invention, in a stacked-type all-solid-state secondary battery, it is possible to reduce bias in the pressure applied to each battery unit during charging and discharging. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram illustrating a configuration of an all-solid-state secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an exploded view of the all-solid-state secondary battery according to the embodiment. [Diagram 3] FIG. 2 is a diagram showing a schematic configuration of a battery body of the all-solid-state secondary battery according to the embodiment; [Figure 4] FIG. 13 is a diagram illustrating a configuration of a battery body of an all-solid-state secondary battery according to another embodiment. [Diagram 5] FIG. 2 is a diagram showing a schematic configuration of a sample of an all-solid-state secondary battery used in the examples. [Figure 6] FIG. 4 is a graph showing the results of evaluation of battery characteristics in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, one embodiment of the all-solid-state secondary battery of the present invention will be described.
[0022] The all-solid-state secondary battery 100 of this embodiment is a so-called lithium secondary battery that is charged and discharged by the movement of lithium ions between a positive electrode and a negative electrode. As shown in Fig. 1 and Fig. 2, the all-solid-state secondary battery 100 includes a battery case C and a battery main body 1 housed in the battery case C.
[0023] The battery case C is rectangular (cuboid) and made of a metal such as aluminum. The battery case C has three pairs of opposing faces with different areas, and the opposing face S with the smallest area serves as the bottom face. A positive terminal P and a negative terminal N electrically connected to the battery body 1 are provided on one of the bottom faces.
[0024] The battery body 1 is a laminated type battery body formed by stacking a plurality of (here, 13) battery units 11, and has a substantially rectangular parallelepiped shape. As shown in Figs. 2 and 3, each battery unit 11 is plate-shaped, and is formed by stacking a positive electrode layer 111, a solid electrolyte layer 112, and a negative electrode layer 113 in this order in the height direction. The battery body 1 is formed by stacking a plurality of such battery units 11 along the height direction. The battery body 1 is accommodated in a battery case C such that the stacking direction of the battery units 11 coincides with the height direction of the battery case C (i.e., the direction perpendicular to the bottom surface).
[0025] (Positive electrode layer) The positive electrode layer 111 includes a positive electrode current collector layer 111a and a positive electrode active material layer 111b arranged in this order toward the negative electrode layer 113.
[0026] The positive electrode collector layer 111a is a sheet, foil, or plate having a rectangular shape in plan view. The material constituting the positive electrode collector layer 111a is not particularly limited, and any known material that can be used in an all-solid-state battery can be appropriately used. Examples of the material include stainless steel, aluminum, copper, nickel, iron, titanium, carbon, and alloys thereof.
[0027] The positive electrode active material layer 111b reversibly absorbs and releases lithium ions. The positive electrode active material layer 111b contains at least a positive electrode active material, and preferably further contains a solid electrolyte. In addition, if necessary, the positive electrode active material layer 111b may contain additives used in the positive electrode active material layer 111b of an all-solid-state battery, such as a known conductive assistant, binder, filler, and dispersant.
[0028] The material of the positive electrode active material is not particularly limited, and known materials that can be used in all-solid-state batteries can be appropriately used. For example, the positive electrode active material can be formed using lithium salts such as lithium cobaltate, lithium nickelate, lithium nickel cobaltate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganate, lithium iron phosphate, nickel sulfide, copper sulfide, sulfur, iron oxide, or vanadium oxide. These positive electrode active materials may be used alone or in combination of two or more.
[0029] Further, the positive electrode active material preferably contains a lithium salt of a transition metal oxide having a layered rock salt structure among the above-described lithium salts. Here, "layered" represents a thin sheet-like shape. Also, "rock salt structure" represents a sodium chloride-type structure which is a type of crystal structure. Specifically, it represents a structure in which the face-centered cubic lattices formed by each of the cations and anions are displaced from each other by 1 / 2 of the edge of the unit cell.
[0030] Examples of such lithium salts of transition metal oxides having a layered rock salt structure include, for example, LiNi x Co y Al z O2 (NCA), or LiNi x Co y Mn z O2 (NCM) (where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1), etc., lithium salts of ternary transition metal oxides.
[0031] When the positive electrode active material contains a lithium salt of a ternary transition metal oxide having the above-described layered rock salt structure, the energy density and thermal stability of the all-solid-state secondary battery 100 can be improved.
[0032] The positive electrode active material may be covered with a coating layer. Here, the coating layer of the present embodiment may be any known coating layer for the positive electrode active material of the all-solid-state secondary battery 100. Examples of the coating layer include, for example, Li2O-ZrO2.
[0033] Furthermore, when the positive electrode active material is formed of a lithium salt of a ternary transition metal oxide such as NCA or NCM and contains nickel (Ni) as the positive electrode active material, it is possible to increase the capacity density of the all-solid-state secondary battery 100 and reduce metal elution from the positive electrode active material. As a result, the all-solid-state secondary battery 100 according to this embodiment can improve the long-term reliability and cycle characteristics.
[0034] Here, examples of the shape of the positive electrode active material include particle shapes such as a perfect sphere and an oval sphere. The particle size of the positive electrode active material is not particularly limited, and may be within a range applicable to the positive electrode active material of a conventional all-solid-state secondary battery. The content of the positive electrode active material in the positive electrode active material layer 111b is also not particularly limited, and may be within a range applicable to the positive electrode layer 111 of a conventional all-solid-state secondary battery.
[0035] Examples of the conductive assistant that can be mixed into the positive electrode active material layer 111b include graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, etc. Examples of the binder that can be mixed into the positive electrode active material layer 111b include styrene butadiene rubber, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc. Furthermore, examples of the filler, dispersant, ion conductive assistant, etc. that can be mixed into the positive electrode active material layer 111b include known materials that are generally used in electrodes of all-solid-state secondary batteries.
[0036] (solid electrolyte layer) The solid electrolyte layer 112 is disposed between the positive electrode layer 111 and the negative electrode layer 113 (specifically, between the positive electrode active material layer 111b and the negative electrode active material layer 113a). The solid electrolyte layer 112 is a sheet, foil, or plate having a rectangular shape in plan view, and contains a solid electrolyte capable of moving ions. The solid electrolyte layer 112 contains a solid electrolyte capable of moving ions. The material of the solid electrolyte is not particularly limited, and any known material that can be used in an all-solid-state battery can be appropriately used, such as a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte.
[0037] Examples of sulfide-based solid electrolyte materials that constitute the solid electrolyte include Li2S-P2S5, Li2S-P2S5-Li X (X is a halogen element, e.g., I, Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers, and M is any of P, Si, Ge, B, Al, Ga, and In). Here, the sulfide-based solid electrolyte material is produced by processing the starting material (e.g., Li2S, P2S5, etc.) by a melt quenching method, a mechanical milling method, or the like. In addition, after these processings, a heat treatment may be further performed. The solid electrolyte may be amorphous, crystalline, or a mixture of both.
[0038] In addition, among the above-mentioned sulfide solid electrolyte materials, it is preferable to use a material containing sulfur and one or more elements selected from the group consisting of silicon, phosphorus, and boron as the solid electrolyte. This improves the lithium conductivity of the solid electrolyte layer 112, and improves the battery characteristics of the all-solid-state secondary battery 100. In particular, it is preferable to use a solid electrolyte containing at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements, and it is more preferable to use a solid electrolyte containing Li2S-P2S5 in particular.
[0039] Here, when a sulfide-based solid electrolyte material containing Li2S-P2S5 is used to form the solid electrolyte, the mixture molar ratio of Li2S and P2S5 may be selected in the range of, for example, Li2S:P2S5=50:50 to 90:10. The solid electrolyte layer 112 may further contain a binder. Examples of the binder contained in the solid electrolyte layer 112 include styrene butadiene rubber, polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene oxide. The binder in the solid electrolyte layer 112 may be the same as or different from the binder in the positive electrode active material layer 111b.
[0040] (Negative electrode layer) The negative electrode layer 113 includes a negative electrode current collector layer 113b and a negative electrode active material layer 113a, which are arranged in this order toward the positive electrode layer 111.
[0041] The negative electrode collector layer 113b is a sheet, foil, or plate having a rectangular shape in plan view. The material constituting the negative electrode collector layer 113b is not particularly limited, and any known material that can be used in an all-solid-state battery can be appropriately used. Examples of the material include stainless steel, aluminum, copper, nickel, iron, titanium, and carbon.
[0042] The negative electrode active material layer 113a contains one or more negative electrode active materials that form an alloy or a compound with lithium. When the all-solid-state secondary battery 100 of this embodiment is overcharged, the negative electrode active material contained in the negative electrode active material layer 113a and the lithium ions transferred from the positive electrode layer 111 form an alloy or a compound, and metallic lithium is precipitated on one or both surfaces of the negative electrode active material layer 113a.
[0043] Specifically, in the initial stage of charging, the negative electrode active material that forms an alloy or compound with lithium in the negative electrode active material layer 113a forms an alloy or compound with lithium ions, so that lithium is absorbed in the negative electrode active material layer 113a. After that, after the capacity of the negative electrode active material layer 113a is exceeded, metallic lithium is precipitated on one or both surfaces of the negative electrode active material layer 113a. A metal layer is formed by this metallic lithium. Since the metallic lithium is formed while diffusing through the negative electrode active material that can form an alloy or compound, it is not dendritic (dendrite-like) but is formed uniformly along the surface of the negative electrode active material layer 113a. During discharge, the metallic lithium in the negative electrode active material layer 113a and the metal layer is ionized and moves to the positive electrode active material layer 111b. As a result, metallic lithium can be used as the negative electrode active material, and the energy density is improved.
[0044] In this embodiment, the total thickness of the negative electrode current collector and the negative electrode active material layer 113a included in each battery unit 11 is configured to be smaller than the thickness of the metallic lithium layer deposited between the negative electrode current collector and the negative electrode active material layer 113a when the all-solid-state battery is in a fully charged state.
[0045] Here, the specific capacity per unit area of the positive electrode layer 111 is defined as X [mAh / cm 2 ] so that the thickness of the metallic lithium layer deposited in the negative electrode layer 113 in the stacking direction in a fully charged state is 4.85×X [μm].
[0046] The material of the negative electrode active material for realizing such a function may further contain at least one selected from the group consisting of amorphous carbon, Au, Pt, Pd, Si, Al, Bi, Sn, In, and Zn. Specific examples of amorphous carbon include carbon black such as acetylene black, furnace black, and ketjen black, and graphene.
[0047] The shape of the negative electrode active material is not particularly limited, and may be granular, or may be a uniform layer, such as a plating layer. In the former case, lithium ions pass through the gaps between the granular negative electrode active material particles, and a lithium metal layer can be formed between the negative electrode active material layer 113a and the negative electrode current collector. On the other hand, in the latter case, a metal layer is precipitated between the negative electrode active material layer 113a and the solid electrolyte layer 112.
[0048] The negative electrode active material layer 113a may further contain a binder. By containing the binder, the negative electrode active material layer 113a can be stabilized on the negative electrode current collector. Examples of materials constituting the binder include resin materials such as styrene butadiene rubber, polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene. The binder may be composed of at least one type selected from these resin materials.
[0049] The negative electrode active material may also contain additives used in conventional all-solid-state lithium secondary batteries, such as fillers, dispersants, and ion conductive agents.
[0050] The battery body 1 includes a positive electrode current collector terminal 12 electrically connected to the positive electrode current collector layer 111a of each battery unit 11, and a negative electrode current collector terminal 13 electrically connected to the negative electrode current collector layer 113b of each battery unit 11. The positive electrode current collector terminal 12 and the negative electrode current collector terminal 13 are both plate-shaped and are provided to extend along the stacking direction of the battery body 1. The positive electrode current collector terminal 12 and the negative electrode current collector terminal 13 are connected to a positive electrode terminal P and a negative electrode terminal N protruding from the battery case C, respectively. The power generated in each battery unit 11 can be taken out to the outside through the positive electrode current collector terminal 12 and the negative electrode current collector terminal 13. Each battery unit 11 has a positive electrode current collector tab 12a and a negative electrode current collector tab 13a protruding in a direction perpendicular to the stacking direction, and these are electrically connected to the positive electrode current collector terminal 12 and the negative electrode current collector terminal 13, respectively. In this embodiment, the battery body 1 is configured so that the battery units 11 are connected in parallel to each other.
[0051] (buffer layer) Thus, in the all-solid-state secondary battery 100 of this embodiment, the battery body 1 includes one or more buffer layers 14 provided between adjacent battery units 11. In this embodiment, the buffer layers 14 are provided between all adjacent battery units 11 and between the battery units 11 and the battery case C at both ends in the stacking direction.
[0052] Each buffer layer 14 is a sheet or plate having a rectangular shape in plan view, and is provided so that its thickness direction coincides with the stacking direction of the battery units 11. When viewed from the stacking direction of the battery units 11, the area of each buffer layer 14 is larger than the area of each battery unit 11, and each buffer layer 14 is provided so as to cover a portion of the battery unit 11 excluding the positive electrode current collector tab 12a and the negative electrode current collector tab 13a. The total thickness of each buffer layer 14 is set so as to be larger than the total amount of change in thickness of each battery unit 11 along the stacking direction due to charging and discharging.
[0053] The buffer layer 14 absorbs the volume change (expansion) of the battery unit 11 accompanying charging and discharging, and is made of an elastically deformable member, and more specifically, is made of a material having a smaller elastic modulus than the positive electrode current collector and the negative electrode current collector. The material constituting such a buffer layer 14 is preferably one having a stress-displacement curve with a slope of 200 MPa or less at 80% or less of displacement, more preferably one having a stress-displacement curve with a slope of 50 MPa or less at 80% or less of displacement, and even more preferably one having a stress-displacement curve with a slope of 10 MPa or less at 50% or less of displacement. Examples of materials for such a buffer layer 14 include, but are not limited to, epoxy resin, acrylic resin, polyimide resin, polyester resin, polypropylene resin, polyamide resin, polystyrene resin, polyvinyl chloride resin, polycarbonate resin, fluororesins such as PTFE, silicone rubber, and the like. Each buffer layer 14 may be made of a single material, or may be made of a combination of multiple materials. Furthermore, each buffer layer 14 may be made of the same material, or may be made of different materials. In this embodiment, the buffer layer 14 is made of an insulating material to insulate the battery units 11 from each other. Such an insulating material has a surface resistance of 1.0×10 17 Ω cm 2 The above materials are preferable. Specific examples include fluororesins such as PTFE, silicone rubber, and the like.
[0054] Furthermore, in the battery body 1 of the present embodiment, an insulating film having a thickness smaller than that of the buffer layer 14 is provided between the battery unit 11 and the buffer layer 14. Examples of materials constituting such an insulating film include, but are not limited to, a PET (polyethylene terephthalate) film, a PTFE (polytetrafluoroethylene) film, a Kapton film, a polyimide film, and an imide film.
[0055] According to the all-solid-state secondary battery 100 of this embodiment configured in this manner, the buffer layer 14 is provided between each battery unit 11, so that when the all-solid-state secondary battery 100 is charged and the battery unit 11 expands, the pressure can be dispersed, and bias in the pressure applied to each battery unit 11 due to charging and discharging can be reduced. This makes it possible to suppress cracks and deformations in the electrolyte layer caused by repeated charging and discharging, and to suppress deterioration of battery characteristics such as cycle characteristics.
[0056] The present invention is not limited to the above-described embodiment.
[0057] In the battery body 1 of the above embodiment, the battery units 11 are connected in parallel to each other, but this is not limited thereto. In other embodiments, the battery units 11 may be connected in series to each other. In this case, it is preferable that each buffer layer 14 is made of a conductive material and current is passed between each battery unit 11. Such a conductive material has a surface resistance of 0.1 Ω / cm 2 The following materials are preferable. Specifically, copper foil, aluminum foil, conductive double-sided tape, etc. Also, the battery units 11 may be connected in parallel and in series.
[0058] In the above embodiment, the battery body 1 is housed such that the opposing surface of the battery case C having the smallest area is the bottom surface and the height direction and the stacking direction coincide with each other, but this is not limited to the above. In other embodiments, the battery body 1 may be housed such that the opposing surface of the battery case C other than the opposing surface having the smallest area is the bottom surface and the height direction and the stacking direction coincide with each other.
[0059] In the battery body 1 of the above embodiment, the buffer layers 14 are provided between all adjacent battery units 11 and between the battery units 11 and the battery case C at both ends in the stacking direction, but this is not limited to the above. In other embodiments, the buffer layers 14 may be provided so as to sandwich the multiple battery units 11 from above and below in the stacking direction, as shown in Fig. 4 for example. In this case, an insulating layer such as the insulating film described above may be provided between each battery unit 11.
[0060] In another embodiment of the battery body 1, a metallic lithium layer does not need to be deposited in the negative electrode layer 113. For example, when a material capable of reversibly absorbing and releasing more lithium ions, such as silicon, is used, the volume of the negative electrode active material changes several times. In this embodiment, the total value of the thicknesses of the positive electrode layer 111, the solid electrolyte layer 112, and the negative electrode layer 113 of each battery unit 11 is configured to be larger in a fully charged state than in a discharged state. EXAMPLES
[0061] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and may be modified within the scope of the above and below-described aims, and all such modifications are within the technical scope of the present invention.
[0062] <Example 1> The effect of the presence or absence of a buffer layer between battery units on the battery characteristics was evaluated.
[0063] 1. Manufacturing of stacked all-solid-state secondary batteries (1) Preparation of the positive electrode structure LiNi as a positive electrode active material 0.8 Co 0.15 Al 0.05 O2(NCA) ternary powder, Li2S-P2S5 (80:20 mol%) amorphous powder as a sulfide-based solid electrolyte, and vapor-grown carbon fiber powder as a positive electrode layer conductive material (conductive additive) were weighed out in a mass ratio of 60:35:5 and mixed using a planetary centrifugal mixer.
[0064] Next, a dehydrated xylene solution in which SBR was dissolved as a binder was added to this mixed powder so that the SBR was 5.0 mass% relative to the total mass of the mixed powder to generate a primary mixed liquid. Furthermore, a suitable amount of dehydrated xylene for viscosity adjustment was added to this primary mixed liquid to generate a secondary mixed liquid. Furthermore, in order to improve the dispersibility of the mixed powder, zirconia balls with a diameter of 5 mm were put into the secondary mixed liquid so that the space, the mixed powder, and the zirconia balls each occupied 1 / 3 of the total volume of the kneading vessel. The tertiary mixed liquid thus generated was put into a planetary centrifugal mixer and stirred at 3000 rpm for 3 minutes to generate a positive electrode layer coating liquid.
[0065] Next, a 20 μm thick aluminum foil collector was prepared as a positive electrode collector, and the positive electrode collector was placed on a tabletop screen printer. The positive electrode layer coating liquid was applied onto the sheet using a metal mask with a hole size of 2.0 cm × 2.0 cm and a thickness of 150 μm. The sheet on which the positive electrode layer coating liquid was applied was then dried on a hot plate at 60 ° C for 30 minutes, and then vacuum dried at 80 ° C for 12 hours. This formed a positive electrode layer on the positive electrode collector. The total thickness of the positive electrode collector and the positive electrode layer after drying was about 165 μm.
[0066] (2) Preparation of negative electrode structure Graphite powder (vacuum dried at 80°C for 24 hours) as the negative electrode active material and PVDF as the binder were weighed out in a mass ratio of 95.0:5.0. These materials and an appropriate amount of NMP were then put into a planetary centrifugal mixer, stirred at 3000 rpm for 3 minutes, and then degassed for 1 minute to produce a negative electrode layer coating solution.
[0067] Next, a copper foil current collector having a thickness of 16 μm was prepared as a negative electrode current collector, and the negative electrode layer coating liquid was applied onto the copper foil current collector using a blade. The thickness (gap) of the negative electrode layer coating liquid on the copper foil current collector was about 150 μm.
[0068] The sheet coated with the negative electrode layer coating liquid was placed in a dryer heated to 80° C. and dried for 15 minutes. The dried sheet was then vacuum-dried at 80° C. for 24 hours. This produced a negative electrode structure. The thickness of the negative electrode structure was about 140 μm.
[0069] (3) Preparation of electrolyte layer A dehydrated xylene solution in which SBR was dissolved was added to an amorphous powder of Li2S-P2S5 (80:20 mol%) as a sulfide-based solid electrolyte so that the SBR was 2.0 mass% relative to the total mass of the mixed powder to generate a primary mixed liquid. An appropriate amount of dehydrated xylene was added to this primary mixed liquid to adjust the viscosity to generate a secondary mixed liquid. Furthermore, to improve the dispersibility of the mixed powder, zirconia balls with a diameter of 5 mm were added to the tertiary mixed liquid so that the space, mixed powder, and zirconia balls each occupied 1 / 3 of the total volume of the kneading vessel. The tertiary mixed liquid thus generated was added to a planetary centrifugal mixer and stirred at 3000 rpm for 3 minutes to generate an electrolyte layer coating liquid.
[0070] The negative electrode structure was placed on a tabletop screen printer, and the electrolyte layer coating liquid was applied onto the negative electrode structure using a 500 μm metal mask. The sheet on which the electrolyte layer coating liquid was applied was then dried on a hot plate at 40 ° C for 10 minutes, and then vacuum dried at 40 ° C for 12 hours. This formed an electrolyte layer on the negative electrode structure. The total thickness of the electrolyte layer after drying was about 300 μm.
[0071] (4) Preparation of a single cell The sheet consisting of the negative electrode structure and the electrolyte layer and the positive electrode structure were punched out with a Thomson blade, and the electrolyte layer of the sheet and the positive electrode layer of the positive electrode structure were bonded together by a dry lamination method using a roll press with a roll gap of 150 μm to produce a single cell (battery unit) of an all-solid-state secondary battery. The layer thickness of this single cell was about 400 μm.
[0072] (5) Fabrication of stacked all-solid-state secondary batteries The obtained single cells were stacked to produce two stacked-type all-solid-state secondary batteries. As shown in Figure 5(a), for one sample, a PTFE sheet approximately 500 μm thick was placed between the single cells as a buffer layer, which was then placed in an aluminum laminate film with terminals attached. The cell was then evacuated to 100 Pa using a vacuum machine, and then heat-sealed and packed (sample A). For the other sample, as shown in FIG. 5(b), no buffer layer was provided between the single cells, and these were placed in an aluminum laminate film with terminals attached. The cells were then evacuated to 100 Pa using a vacuum machine, and then heat-sealed and packed (sample B).
[0073] 2. Battery characteristic evaluation The charge / discharge capacity (mAh) of the fabricated all-solid-state secondary batteries of Sample A and Sample B was measured using a charge / discharge evaluation device (TOSCAT-3100, manufactured by Toyo Systems). Charge / discharge was performed in an environment of 60°C. The charge / discharge capacity of each sample was measured by charging to 4.25 V at a current of 0.1 mA and discharging to 2.50 V at a current of 0.1 mA. The measurement results are shown in Figure 6.
[0074] As can be seen from Figure 6, in the all-solid-state secondary battery of sample A, in which a buffer layer was inserted between the unit cells and stacked, the charge capacity and discharge capacity were equal. In contrast, in the all-solid-state secondary battery of sample B, in which no buffer layer was inserted between the unit cells, the charge capacity increased due to micro-short circuits and the efficiency decreased. This confirmed that short circuits can be suppressed by providing a buffer layer between the unit cells, and the cycle characteristics of the all-solid-state secondary battery can be improved. [Explanation of symbols]
[0075] 100 All-solid-state lithium secondary battery 1. Battery body 11 Battery unit 111 Positive electrode layer 111a Positive electrode current collector layer 111b...Positive electrode active material layer 112...Solid electrolyte layer 113 Negative electrode layer 113a...Negative electrode active material layer 113b...Negative electrode current collector layer 14 ··· Buffer layer
Claims
1. a stacked-type all-solid-state secondary battery in which a plurality of battery units each including a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in this order are stacked in the stacking direction, A buffer layer is provided between adjacent battery units, each of the battery units is charged and discharged by the movement of lithium ions between the positive electrode layer and the negative electrode layer; an all-solid-state secondary battery in which, in a fully charged state, a total value of thicknesses, along the stacking direction, of a negative electrode current collector and a negative electrode active material layer provided in the negative electrode layer is smaller than a thickness, along the stacking direction, of a metallic lithium layer deposited between the negative electrode current collector and the negative electrode active material layer.
2. 2. The all-solid-state secondary battery according to claim 1, wherein a total thickness of the buffer layers along the stacking direction is greater than a total amount of change in thickness of the battery units along the stacking direction due to charging and discharging.
3. The all-solid-state secondary battery according to claim 1 or 2, wherein the buffer layer has an elastic modulus smaller than those of the positive electrode layer and the negative electrode layer.
4. 2. The all-solid-state secondary battery according to claim 1, wherein the specific capacity per unit area of the positive electrode layer is X [mAh / cm2], and the thickness of the metallic lithium layer in the stacking direction in a fully charged state is 4.85×X [μm] or more.
5. The battery pack further includes a rectangular parallelepiped case that houses the battery units and the buffer layer, 5. The all-solid-state secondary battery according to claim 1, wherein the plurality of battery units and the buffer layer are housed in the case so as to be stacked in a height direction, with the opposing surface having the smallest area among the three sets of opposing surfaces provided in the case serving as a bottom surface.
6. The all-solid-state secondary battery according to any one of claims 1 to 5, wherein an area of the buffer layer is larger than an area of the battery unit when viewed from the stacking direction.
7. the plurality of battery units are electrically connected in parallel to each other, The all-solid-state secondary battery according to any one of claims 1 to 6, wherein the buffer layer provided between the battery units is made of an insulating material.
8. The all-solid-state secondary battery according to claim 7 , wherein an insulating film having a thickness smaller than that of the buffer layer is provided between the battery units and the buffer layer adjacent to each other.
9. the plurality of battery units are electrically connected in series with each other, The all-solid-state secondary battery according to any one of claims 1 to 6, wherein the buffer layer provided between the battery units is made of a conductive material.
Citation Information
Patent Citations
Stacked battery
EP3386006A1
All solid thin film laminated battery
JP2004273436A
Nonaqueous electrolyte battery
JP2011086554A
All-solid battery
JP2015232976A
All-solid battery and manufacturing method of the same
JP2019061861A